PADDISSENGENG DAN KEDUDUKANNYA DALAM MASYARAKAT BUGIS (TELAAH CATATAN A. MAPIASSE GULE DALAM 100 ADA PAPPASENG TO RIYOLO) - Agustang K (IAIN TERNATE, 2020)
Knowledge Occupies A Very Important Position In The Teachings Of Islam, This Can Be Seen From The Many Verses Of The Koran That View Knowledgeable People In A High And Noble Position Besides The Prophetic Traditions Which Have Encouraged Many People To Continue To Study. In The Koran, The Word Science And The Words Invented Are Used More Than 780 Times. This Means That The Teachings Of Islam As Reflected In The Koran Are Very Thick With Nuances Related To Science, So That They Can Become An Important Characteristic Of Islam. Not Only That, For Those Who Have Knowledge, They Will Get Several Degrees Of Glory Along With Those Who Believe. The Faith That A Person Has Will Be A Driving Force To Seek Knowledge, And The Knowledge That A Person Has Will Make Him Realize How Small Humans Are In Front Of Allah, So That He Will Feel Guilt Towards Allah SWT When He Does Things That Are Prohibited. Demanding Knowledge Is Also A Representation Of The First Verse Of The Qur'an, Namely QS. Al-Alaq Verses 1-5, The Essence Of Which Contains The Command To Read, Read Through The Qalam. Given The Importance Of Science In Islam, Every Muslim Is Obliged To Have A Burning Spirit And Earnestly In Studying. This Enthusiasm And Sincerity Must Be Built Firmly In The Heart Of Every Muslim So That Nothing Is Easily Distracted. In The Pesantren Tradition, Students Are Required To Memorize Arabic Aphorisms Which Are Often Known As Mahfudzaat As A Medium To Arouse The Spirit Of The Students. These Pearl Words Are Made Tiered According To The Needs Of The Pesantren. Because Of The Importance Of The Mahfudzaat Book, Many Pesantren In Indonesia Have Made The Mahfudzaat Book A Mandatory Guide For Later Memorizing. Because Of This, The Author Tries To Elaborate On Mahfudzaat's Book In Order To Find The Concept Of The Mujahada Lithalab Al-Ilmi Contained In It. This Paper Uses The Library Research Method By Tracing The Literature Related To The Mahfudzhat Book By The Turos Pustaka Team. The Information Obtained Is Then Processed By Qualitative Data Analysis Techniques To Then Draw A Conclusion. From The Results Of This Search, It Was Found That The Concept Of Mujahadah Li Thalab Al-Ilmi In The Mahfudzat Book Is That Learning Must Be Structured, Patient, There Is A Balance In The Life Of The Hereafter And Prioritizes Morality.